ʿAlī ibn Sahl Rabban aṭ-Ṭabarī: The Indian Books : A new edition of the Arabic text and first-time English translation - aṭ-Ṭabarī, ʿAlī ibn Sahl Rabban, (Islamic Philosophy, Theology and Science. Texts and Studies ;, 2022)
ʿAlī ibn Sahl aṭ-Ṭabarī's Indian Books, completed in Samarra in 850 CE, offer a unique, interpretative summary of Ayurvedic medicine, as he understood it on the basis of now lost Arabic translations from Sanskrit.